Fabrication and properties of transparent Nd:YAG ceramics - Ang, Kristy Yu Xin (2018)
Transparent ceramics have been known to be one of the best material for solid state lasers application. Researchers all over the worldhave shown huge interest in researching Solid state laser ceramics. This is because it is known for its flexibility to be doped with different type of elements and has excellent transmittance. It has been widely used as an application for solid state lasers. This project is to evaluate how sintering temperature affect the transparency of YAG ceramics as well as the morphology of co-precipitated powders. Both factors are studied to reduce the porosity in order to attain transparent ceramic for solid-state laser application. This work consists of the fabrication of neodymium-doped yttrium aluminum garnet; Nd:Y3Al5O12 (Nd:YAG) transparent ceramics via Soild state reaction method. Followed by sintering to produce the final transparency samples, the samples then undergo thermal etching and polishing. Lastly, the transparency ceramics samples are then characterized using tools such as UV-VIS spectroscopy, Scanning Electron Microscopy (SEM) and X-ray Diffraction (XRD). Porosity and optical transmittance of the samples were determined based on the microstructure of the samples. These are the factors needed to be considered when producing high quality transparent ceramic product.